Zaposlitev in delovne razmere na področju socialnega varstva - Rihter, Liljana (Socialno delo, 2016)
In recent years, some important changes of legislation in the field of social protection have been adopted. The government has passed a law including austerity measures in the area of salaries and promotions in the public sector. Previous studies only show the effects of changes to users. In the article, the results are presented of the qualitative (meta) analysis of the research findings of the final theses of the students from the Faculty of Social Work between 2012 and 2015, which addressed topics such as employment in the field of social protection, working conditions and quality of working life. The results show that employees have more difficulties meeting particular needs of "having" (salary, promotion). In some environments they feel less secure because of threats of users. And it is also difficult to meet the needs of "being" (fewer opportunities for professional development). An area in which changes in the laws and savings haven't had (yet) a significant impact are the needs of "loving". Relations between employees remain one aspect which is generally well rated. Based on identified weaknesses, systemic changes are suggested that would allow for better working conditions, as well as organizational changes within the working environment that would enable more support to staff to carry out professional work, which will respond to the needs of users.
Keywords: social protection; socialne varstvo; employees; zaposleni; stres; stress; izgorelost; burnout; delovno življenje; quality of working life